Gymnopus violaceigregarius (Omphalotaceae, Agaricales, Basidiomycota): a new species from Pakistan - Qasmi, Arshia Bano; Izhar, Aiman; Khalid, Abdul Nasir (Phytotaxa, 2025)
In this study, a new species in Gymnopus is described herein, based on collections made from forests of Kumrat Valley, Pakistan. This species is characterized by small to medium-sized, fragile, fasciculate basidiomata, violet, black to dark reddish-brown stipes, obovoid, ellipsoidal to oblong basidiospores 4.7–8.8 × 3–4.2 µm in size, simple diverticulate pileipellis and stipitipellis. The phylogeny inferred from the concatenated internal transcribed spacers (ITS) and the large subunit (nrLSU) of the nuclear ribosomal DNA, also support the finding that G. violaceigregarius is sister species of G. gansuensis reported from China but the new species is distinct from G. gansuensis and all other known species within the genus Gymnopus with significant bootstrap and Bayesian support. A full description, color photographs, illustrations, phylogenetic tree showing the position of G. violaceigregarius and comparison to similar species is provided.